Human sFLT1 Leads to Severe Changes in Placental Differentiation and Vascularization in a Transgenic hsFLT1/rtTA FGR Mouse Model - Vogtmann, Rebekka; Kühnel, Elisabeth; Dicke, Nikolai; Verkaik-Schakel, Rikst Nynke; Plösch, Torsten; Schorle, Hubert; Stojanovska, Violeta; Herse, Florian; Köninger, Angela; Kimmig, Rainer; Winterhager, Elke; Gellhaus, Alexandra (Frontiers in Endocrinology, 2019)
The anti-angiogenic soluble fms-like tyrosine kinase 1 (sFLT1) is one of the candidates in the progression of preeclampsia, often associated with fetal growth restriction (FGR). Therapeutic agents against preeclampsia with/without FGR, as well as adequate transgenic sFLT1 mouse models for testing such agents, are still missing. Much is known about sFLT1–mediated endothelial dysfunction in several tissues; however, the influence of sFLT1 on placental and fetal development is currently unknown. We hypothesize that sFLT1 is involved in the progression of FGR by influencing placental differentiation and vascularization and is a prime candidate for interventional strategies. Therefore, we generated transgenic inducible human sFLT1/reverse tetracycline-controlled transactivator (hsFLT1/rtTA) mice, in which hsFLT1 is ubiquitously overexpressed during pregnancy in dams and according to the genetics in homozygous and heterozygous fetuses. Induction of hsFLT1 led to elevated hsFLT1 levels in the serum of dams and on mRNA level in all placentas and hetero-/homozygous fetuses, resulting in FGR in all fetuses at term. The strongest effects in respect to FGR were observed in the hsFLT1/rtTA homozygous fetuses, which exhibited the highest hsFLT1 levels. Only fetal hsFLT1 expression led to impaired placental morphology characterized by reduced placental efficiency, enlarged maternal sinusoids, reduced fetal capillaries and impaired labyrinthine differentiation, associated with increased apoptosis. Besides impaired placental vascularization, the expression of several transporter systems, such as glucose transporter 1 and 3 (Glut-1; Glut-3); amino acid transporters, solute carrier family 38, member 1 and 2 (Slc38a1; Slc38a2); and most severely the fatty acid translocase Cd36 and fatty acid binding protein 3 (Fabp3) was reduced upon hsFLT1 expression, associated with an accumulation of phospholipids in the maternal serum. Moreover the Vegf pathway showed alterations, resulting in reduced Vegf, Vegfb and Plgf protein levels and increased Bad and Caspase 9 mRNA levels. We suggest that hsFLT1 exerts an inhibitory influence on placental vascularization by reducing Vegf signaling, which leads to apoptosis in fetal vessels, impairing placental differentiation and the nutrient exchange function of the labyrinth. These effects were more pronounced when both the dam and the fetus expressed hsFLT1 and ultimately result in FGR and resemble the preeclamptic phenotype in humans.